A long‐acting isomer of Ac‐SDKP attenuates pulmonary fibrosis through SRPK1‐mediated PI3K/AKT and Smad2 pathway inhibition. Issue 12 (2nd November 2020) - Qiu, Yueyuan; Wang, Zhaowei; Zhang, Xutao; Huang, Ping; Zhang, Wangqian; Zhang, Kuo; Wang, Shuning; He, Lei; Guo, Yanhai; Xiang, An; Zhang, Cun; Hao, Qiang; et al.
Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive, life‐threatening lung disease with a poor prognosis. N‐acetyl‐seryl‐aspartyl‐lysyl‐proline (Ac‐SDKP) is a critical negative regulator of fibrosis development. However, it's extremely short half‐life greatly limits its applications. Previously, we reported an Ac‐SDKP analog peptide in which Asp and Lys residues were replaced with D‐amino acids (Ac‐SDD KD P). Ac‐SDD KD P exhibits better resistance to angiotensin‐1‐converting enzyme (ACE)‐mediated degradation and a longer half‐life than Ac‐SDKP in rat and human sera. The objective of this study was to explore the potential application of Ac‐SDD KD P for the treatment of IPF and to clarify the underlying mechanisms. We found that Ac‐SDD KD P exerted similar antifibrotic effects as Ac‐SDKP on human fetal lung fibroblast‐1 (HFL‐1) proliferation, α‐smooth muscle actin (α‐SMA), collagen I and collagen III expression, and Smad‐2 phosphorylation in vitro. In vivo, Ac‐SDD KD P exhibited significantly greater protective effects against bleomycin‐induced pulmonary fibrosis than Ac‐SDKP in mice. α‐SMA, CD45, collagen I and collagen III expression, and Smad‐2 phosphorylation were significantly decreased in the lungs of Ac‐SDD KD P‐treated but not Ac‐SDKP‐treated mice. Furthermore, a pull‐down experiment was used to screen for molecules that interact with Ac‐SDKP. Co‐immunoprecipitation (Co‐IP) and computer‐based molecular docking experiments demonstrated an interaction between Ac‐SDKP or Ac‐SDD KD P (Ac‐SDKP/Ac‐SDD KD P) and serine/arginine‐rich protein‐specific kinase 1 (SRPK1) that caused inhibition SRPK1‐mediated phosphatidylinositol‐3 kinase/ serine/threonine kinase (PIK3/AKT) signaling pathway activation and Smad2 phosphorylation and thereby attenuated lung fibrosis. Our data suggest that long‐acting Ac‐SDD KD P may potentially be an effective drug for the treatment of pulmonary fibrosis. The interacting molecule and antifibrotic mechanism of Ac‐SDKP/Ac‐SDD KD P were also identified, providing an experimental and theoretical foundation for the clinical application of the drug.